2011
DOI: 10.1667/rr2665.1
|View full text |Cite
|
Sign up to set email alerts
|

Impedance-Based Surveillance of Transient Permeability Changes in Coronary Endothelial Monolayers after Exposure to Ionizing Radiation

Abstract: The relative radiation sensitivities of the various compartments of the heart are poorly characterized. Cardiac fibrosis is a common side effect of radiotherapy, suggesting that endothelial barrier function is an important factor in radiation-induced pathology. We employed Electric Cell Substrate Impedance Sensing (ECIS) to assess cytoskeletal rearrangement, permeability changes and endothelial barrier function changes in response to radiation in studies of human coronary arterial endothelial cells (HCAECs). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
(41 reference statements)
0
12
0
1
Order By: Relevance
“…It is possible that biological mechanisms responsible for the low-dose-rate effects differ from those of high-dose-rate effects. In radiation-induced CVD, high doses cause overt damage to the myocardium [39] but at low and moderate doses the main target for damage appears to be the endothelium [40][42], a cell population typified by a long lifespan, slow proliferation rate and high sensitivity to radiation-induced cell killing. The effects of chronic exposure on endothelial cell function are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that biological mechanisms responsible for the low-dose-rate effects differ from those of high-dose-rate effects. In radiation-induced CVD, high doses cause overt damage to the myocardium [39] but at low and moderate doses the main target for damage appears to be the endothelium [40][42], a cell population typified by a long lifespan, slow proliferation rate and high sensitivity to radiation-induced cell killing. The effects of chronic exposure on endothelial cell function are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, the effects of radiation have been studied with diverse endothelial models and methods with regards to endothelial barrier damage or permeability change (15,16), cytoskeleton disruption (17,18), angiogenic capacity impediment (19,20) and premature senescence (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Radiation effects on HUVECs were assessed using electric cell substrate impedance sensing (ECIS) technology. Using this sensitive, continuous bioelectric measurement approach, the laboratory previously described a six-fold decrease in monolayer resistance after wounding and irradiation, observing a statistically significant decrease in resistance after radiation alone [28]. The ECIS instrument passes multiple frequencies of alternating current through gold pads on a planar array affording extremely sensitive, continuous, non-invasive recordings of monolayer resistance [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…Impedance based measurements of skin, as a simple, rapid, and accessible triage modality, could be of great benefit in a radiation emergency response. It is known that endothelial monolayers prepared from the human coronary endothelium respond to ionizing radiation by changing shape and permeability with relatively early kinetics [28]. Other investigators have observed that small sections of vasculature obtained in biopsy can report systemic pathologies of the donor with good fidelity [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation